2005
DOI: 10.3354/meps302187
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use and demographic population structure of elasmobranchs at a Caribbean atoll (Glover’s Reef, Belize)

Abstract: A 5 yr spring and summer survey (July 2000 to May 2004) of the elasmobranch fauna of Glover's Reef Marine Reserve, Belize, documents the use of this oceanic atoll by at least 12 elasmobranch species, including early life-stages of nurse sharks Ginglymostoma cirratum, Caribbean reef sharks Carcharhinus perezi, lemon sharks Negaprion brevirostris, and southern stingrays Dasyatis americana. Elasmobranch abundance was sampled in 3 atoll macrohabitats (deep lagoon, ocean reef, shallow lagoon) using standardized lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 28 publications
3
77
1
Order By: Relevance
“…The absence of elasmobranchs in the diet of I. oxyrinchus helps to corroborate results obtained by Maia et al (2006). As Pikitch et al (2005) state, this absence may be credited to the low densities such sharks and other ones present in the oceanic environment, when compared to more complex habitats. Other large predators, such as X. gladius, should also be considered as potential prey for I. oxyrinchus (Stillwell & Kohler 1982, Maia et al 2006, but this fact was not observed in this study.…”
Section: Discussionsupporting
confidence: 74%
“…The absence of elasmobranchs in the diet of I. oxyrinchus helps to corroborate results obtained by Maia et al (2006). As Pikitch et al (2005) state, this absence may be credited to the low densities such sharks and other ones present in the oceanic environment, when compared to more complex habitats. Other large predators, such as X. gladius, should also be considered as potential prey for I. oxyrinchus (Stillwell & Kohler 1982, Maia et al 2006, but this fact was not observed in this study.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, young-ofthe-year grey nurse sharks use shallow-water reef habitat as a refuge from larger species (Dicken et al 2006). Pikitch et al (2005) found that small juvenile Caribbean reef sharks were relatively more common inside lagoons, and larger individuals used shallow fore-reef habitats near deeper water to increase foraging opportunities . Small Caribbean reef sharks also move from shallow forereef habitats during the day into the lagoon at night presumably to reduce predation risk (Chapman et al 2007).…”
Section: Segregation and Habitat Partitioningmentioning
confidence: 99%
“…The spatial and temporal shifts in movement of these predators can affect their prey both directly through ingestion and indirectly through predation risk (Speed et al 2010). The presence of multiple species and size classes of reef sharks on healthy reefs (Nelson & Johnson 1980, Stevens 1984, McKibben & Nelson 1986, Chapman et al 2005, DeAngelis et al 2008 suggests that coexistence arises in part because habitat partitioning occurs at some spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-specific habitat partitioning is common in some species, with many studies concluding that juveniles and adults partition habitats by depth, temperature, salinity, or benthos type (Chapman et al 2005, Pikitch et al 2005, McAuley et al 2007, Yeiser et al 2008, Speed et al 2010. However, few studies have quantified temporal and spatial habitat partitioning among different species, although there is some evidence to support inter-specific partitioning in relation to the distribution of prey (White & Potter 2004), habitat type and season (White & Potter 2004, DeAngelis et al 2008.…”
Section: Introductionmentioning
confidence: 99%